A round table devoted to the early phase of pharmaceutical development was held in Novosibirsk as a part of OpenBio-2022 forum - article Editorial (Разработка и регистрация лекарственных средств)
Experts discussed current opportunities for pharmaceutical development in our country, discussed actual difficulties and the ways for overcoming it.